Fiqhi Lingkungan dalam Peta Pembangunan Hukum Nasional - Samsuddin Samsuddin; Siswanto Siswanto (Al-Tafaqquh: Journal of Islamic Law, 2022)
This research discusses "Environmental Fiqhi in the National Law Map" fiqh is a science that deals with syara's laws, namely those that are practical and their sources are detailed arguments. (fiqhul bi'ah). Environmental pollution is a crime, but because it has not been clearly stated the punishment for environmental pollution in the Qur'an and there is no stipulation in Islamic jurisprudence. the perpetrators of environmental pollution should be punished based on the punishment set by the government. This research uses a descriptive method by describing the information in the relevant library materials. The data collection technique in this research is a documentary technique. Namely, information is extracted through documents from various library materials, then analyzed using content analysis, examining the object of research by analyzing books, essays, magazines, articles, and all forms of communication that can be analyzed.